Multiple criteria decision making applications in environmentally conscious manufacturing and product recovery - Gupta, Surendra M.; Ilgın, Mehmet Ali (CRC Press, Taylor & Francis Group, 2018)
In order to ensure environmentally responsible production and disposal of products, local governments are imposing stricter environmental regulations, some of which even require manufacturers to take back their products at the end of the product's useful life. The multiple Criteria Decision Making Techniques presented in this book can be employed to solve the problems of environment-conscious manufacturers in product design, logistics, disassembly and remanufacturing.